PENGARUH ABSENSI FINGER DAN TIPE KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PT. BISMA SUPER MITRA PALEMBANG - Agustina Marzuki.; Kamsrin Sa'i; Dwi Kasasih (JURNAL KOMPETITIF, 2016)
This research aims to know the influence of finger attendance and leadership type on employee’s job performance of PT. Bisma Super Mitra Palembang. The population of this research is all of the 30 employees. Due to the relatively small number of population, the 30 employees are made into sample as well. The independent variables are finger attendance (X1) and leadership type (X2), while the dependent variable is employee’s job performance (Y) of PT. Bisma Super Mitra Palembang. The collection of data is obtained by delivering questionnaires to all the respondents; furthermore the data is analyzed by using descriptive statistic and inferential statistic. The result shows that the variable frequency distribution of employee’s job performance, finger attendance, and leadership type, all of them is normal distribution. The correlation coefficient (R) of 0.713a  indicates of high correlation. The determination coefficient (Adjusted RSquare) is 0.472 which gives the sense that the 47.2% of job performance variable (Y) can be explained or influenced by the variables of finger attendance (X1) and leadership type (X), while theremaining 52.8% is influenced by factors not examined. Keywords : Employee’s Job Performance, Finger Attendance, Leadership Type